Анализ антропоморфных рентгеновских фантомов для контроля качества рентгенографии органов грудной клетки - Макиенко, А. С.; Аверьянова, Л. А.; Старенький, В. П. (ХНУРЕ, 2019)
This paper discusses the need for quality control in radiographic examinations of human chest organs. A review of existing anthropomorphic phantoms is carried out with software analysis of the parameters of their radiographs for this quality control. In the course of the work, a phantom was shown, which has the most adequate result.
Keywords: фантом рентгеновский; рентгенография; контроль качества